The Role of ICT on SMEs’ Performance - Mariska (Bappenas Working Papers, 2018)
Small and medium enterprises (SMEs) have an important role in economic growth and development in various countries. In line with the increasingly open global economy, SMEs are beginning to expand their market to the international scale, and compete competitively with other SMEs as well as big businesses. This is only possible if SMEs adopt and utilize information, communication, and technology (ICT) and various applications such as e-commerce and e-business. This paper describes a literature study on the role of ICT on the performance of SMEs and constraints in the adoption of ICT which has the potential to inhibit the optimization of ICT utilization by SMEs. As well as, describe the benefits that SMEs have through ICT applications and some inputs as recommendations for the solution of theabove problems.